Socio economical aspects of cultural differentiations of population of ZhetiSuw region - Mukanova, Z. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
This paper refers to analysis of socio-economical analysis of ZhetiSuw region of Almaty oblast. Author tries to deepen contemporary view on the migrational processes in Kazakhstan portraying the historical background of the region. Main point of the paper is to give geo-political and socio-economical overview of the region,population during Soviet times and now,detailed explanation of changing the whole image of ZhetiSuw region. How and why did Kazakh ethnic minorities appeared in different countries. State programs and quotas for oralmans and reasons for the invitations of Kazakhs from different countries. At the same time author tries to show the difficulties of socio-economicalintegration of Kazakh repatriates in to contemporain Kazkastani societyand differences of socio-cultural adaptation between orlamans from different countries. Key words: ZhetiSuw, socio-economic integration, oralmans, socio-cultural adaptaion, Kazakh diaspora.